Establishment of a human induced pluripotent stem cell line (TAUi008-A) derived from a multiple sclerosis patient - Lotila Johanna; Hyvärinen Tarja; Skottman Heli; Airas Laura; Narkilahti Susanna; Hagman Sanna (Elsevier B.V., 2022)
Multiple sclerosis (MS) is a complex autoimmune disease of the central nervous system where the main pathogenetic events include demyelination and axonal degeneration. Here, we generated a human induced pluripotent stem cell (hiPSC) line from peripheral blood mononuclear cells of an MS patient utilizing Sendai virus reprogramming. The produced hiPSC line expressed pluripotency markers, differentiated into three germ layers, showed a normal karyotype and was free of virus vectors, transgenes and mycoplasma. Established hiPSCs are a valuable source for studies of MS disease modeling and drug discovery.